MENATA PENDIDIKAN ISLAM DI SMP NEGERI 1 KOTAPINANG - Puspita, Dea Ayu (Yayasan Pendidikan Islam Akmalia, 2021)
Every educational activity requires the implementation of steps or strategies to achieve goals and expectations effectively and efficiently for every organization, department, madrasah and so on. As explained by Ahmad Sutarmadi that the greatest strength that can bring progress in human life is the enormous desires and hopes that people live and have. It can be explained that, nothing can hinder the huge tide of ideologies that live in society, where that ideology is a vision and mission. With the right vision and mission, an organization (educational institution) can move forward towards the future and can develop, and process. This gives the meaning that how important the vision and mission are in an arrangement in the organization (educational institution). This article discusses the phenomenon that occurs regarding problems that develop related to the arrangement of Islamic education or the concept of Islamic education at SMP Negeri 1 Kotapinang.